2004
DOI: 10.1111/j.1468-3083.2004.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Elephantoid oedema of the eyelids

Abstract: We describe a male patient with rosacea who had a 2-year history of persistent bilateral oedema of the eyelids, leading to an elephantoid condition with blepharoptosis. An upper eyelid blepharoplasty was performed, but swelling progressively recurred over a few months. Based on the case history, clinical appearance and histological findings, rosaceous lymphoedema was considered to be the diagnosis. The latter is a bilateral, solid oedema of the mid-third of the face, regarded as a rare complication of rosacea.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Disruption or loss of elastic fibers, which help to maintain tissue form and structural integrity to lymphatic vessels, 118 may underlie the pathogenesis of polypoid tumors, pendulous swellings and masses shown by lymphedematous tumors. Loss of elastic tissue in localized lymphedema has been described in a handful of cases 22,65,87,91 . For example, Marzano et al 87 showed complete loss of elastic fibers in a rosacea patient who developed massive elephantoid eyelid lymphedema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption or loss of elastic fibers, which help to maintain tissue form and structural integrity to lymphatic vessels, 118 may underlie the pathogenesis of polypoid tumors, pendulous swellings and masses shown by lymphedematous tumors. Loss of elastic tissue in localized lymphedema has been described in a handful of cases 22,65,87,91 . For example, Marzano et al 87 showed complete loss of elastic fibers in a rosacea patient who developed massive elephantoid eyelid lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Histopathologically, lymphedema is a fibroinflammatory process. 7,8 Typically, elephantiasis diffusely involves the body part affected by lymphedema (legs more than arms and genitalia episodically); 8 exceptionally, lymphedema involves circumscribed region of skin producing a solitary, large polyp, indurated (solid) plaque, papillomatous plaque, [69][70][71][72][73][74][75][76][77][78][79][80] pendulous swelling [81][82][83][84][85][86][87][88][89][90] or large, sarcoma-like mass. Herein, we report the clinicopathologic findings of a consecutive series of 24 cases of localized lymphedema (elephantiasis) and review the literature on this phenomenon.…”
mentioning
confidence: 99%
“…Clinical features include nonpitting oedema and erythema particularly on the forehead, gla bella, eyelids, nose, and cheeks (4). Subjective symptoms are usually not so severe, but eyelid involvement may cause facial disfigurement, visual field narrowing, and severe lymphoedema similar to an elephantoid condition (4,5). We present the first case in the English literature of Morbihan disease successfully treated with longterm minocycline monotherapy.…”
Section: Short Communicationmentioning
confidence: 95%
“…Generally, little to no improvement in facial edema is noted with the use of pharmacological agents, leading many clinicians to pursue more invasive, yet also unreliable, treatments such as blepharoplasty, carbon dioxide laser, and local injections. 6,10,11,13,20,21 There are fewer than a handful of publications documenting the use of oral isotretinoin for the treatment of MD, which was first described by Jansen and Plewig 22 in 1997; however, all publications report its use in combination with oral corticosteroids or antihistamines, and treatment duration has varied from 6 to 16 weeks, with daily dosing between 10 and 50 mg. 5,10,22 Also, these treatment regimens were marked by incomplete or transient improvements in clinical findings 6,10,22,23 ; yet the notable improvement in both facial erythema and edema was indicative of oral isotretinoin as a promising therapeutic option compared with other pharmacological agents. It is possible that the conservative dosing and brief treatment duration documented in these reports contributed to the partial success of isotretinoin therapy for MD.…”
Section: Treatmentmentioning
confidence: 99%
“…There have been reports of more invasive interventions, including surgical reduction, carbon dioxide laser blepharoplasty, and radiography, with unpredictable outcomes. 4,6,20,21 To our knowledge, this is the first case series to report the effective use of long-term oral isotretinoin for the treatment of MD with complete and lasting results.…”
Section: Report Of Casesmentioning
confidence: 99%